2020
DOI: 10.1590/1980-265x-tce-2019-0169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stress on the Quality of Life of Hospital Nursing Workers

Abstract: Objective: to analyze the association between socio-occupational characteristics, stress level, and quality of life in hospital Nursing workers. Method: a cross-sectional, quantitative study, with data collected by means of a socio-occupational questionnaire to survey the profile of the workers, the Bianchi Stress Scale to assess stress, and the WHOQOL-Bref to assess quality of life. Results: 180 Nursing workers participated in the research, being 49 nurses and 131 Nursing technicians and assistants, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
5
0
7
Order By: Relevance
“…The relationships experienced by nursing professionals between the socio-occupational interaction and stress have aroused looks for physical, emotional and psychosocial repercussions over the years. However, this finding, present in several studies ( 44 - 46 ) , is consolidated by recognizing that, currently, the psychological domain stands out in the face of other conditioning factors for the illness of nursing professionals ( 47 - 49 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The relationships experienced by nursing professionals between the socio-occupational interaction and stress have aroused looks for physical, emotional and psychosocial repercussions over the years. However, this finding, present in several studies ( 44 - 46 ) , is consolidated by recognizing that, currently, the psychological domain stands out in the face of other conditioning factors for the illness of nursing professionals ( 47 - 49 ) .…”
Section: Discussionmentioning
confidence: 99%
“…As relações vividas pelos profissionais de enfermagem entre a interação sociolaboral e o estresse vêm despertando olhares para repercussões físicas, emocionais e psicossociais ao longo dos anos. Todavia, essa descoberta, presente em vários estudos (44)(45)(46) , consolida-se ao reconhecer que, atualmente, o domínio psicológico se sobressai perante outros fatores condicionantes ao adoecimento dos profissionais de enfermagem (47)(48)(49) .…”
Section: Discussionunclassified
“…The Nursing Profile in Brazil survey showed that there has been a rejuvenation of nursing staff, with 49.6% in the range of 31 to 45 years and 85.1% female, a phenomenon that has occurred for many decades ( 17 ) . It should be noted that being female is associated with higher levels of stress, probably due to the fact that women work double or triple shifts, when considering domestic work ( 18 - 19 ) .…”
Section: Discussionmentioning
confidence: 99%